EFFECT OF SOME PESTICIDE FORMULATIONS ON BLOOD BIOMARKERS, EGG QUALITY AND EGG PRODUCTION OF COTURNIX COTURNIX JAPONICA - Yahaya, Rukayat A.; Gadzama, Ibrahim M. K.; Bello, Abdur-Rahman E.; Owoleke, Veronica A.; Abdulsalam, Sa'adat (FUDMA JOURNAL OF SCIENCES, 2025)
Pesticide treated seeds may be an important source of food for some birds in times of scarcity and thus a route of pesticide ingestion. The present study was carried out to evaluate the effects of different concentrations of seed dressing pesticide formulations on haematological parameters, egg production and egg quality parameters of Japanese quails. Forty- two adult Japanese quails (Coturnix coturnix japonica) were randomly assigned into 7 groups of six quails each. They were fed diets containing equal amounts of millet seeds treated with dress force and apron at 2.0 g/kg, 2.5 g/kg, and 3.0 g/kg of seed for 8 weeks. Results showed significant (p
Keywords: Apron star®; Dress force®; Pesticide; Japanese Quails; Biomarkers